Hubungan Asupan Zat Gizi Makro Vitamin Larut Lemak dan Berat Badan Lahir Dengan Status Gizi Balita di Kecamatan Kanatang Kabupaten Sumba Timur - Nara, Tonda Mbitu; Kencana, I Ketut; Ari Widarti, I Gusti Agung (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Nutrition is one of the important factors that determine the level of health and harmony between physical development and mental development. The level of normal nutritional status is achieved when optimal nutritional needs are met. According to the NTT Health Office in 2015, several areas in NTT that experienced more than 200 cases of malnutrition were in Kupang City, Kupang District, TTS, Alor, Southwest Sumba and East Sumba. Then in Nagakeo, Ngada and Central Sumba the incidence of malnutrition was 50 cases. The purpose of this study was to determine the relationship between intake of macronutrients, fat soluble vitamins, birth weight, and the nutritional status of toddlers in Kanatang District, East Sumba Regency. This study used an observational method with a cross-sectional design with a total sample of 88. The sampling technique used was simple random sampling. Data collection included weighing, measuring height, 24-hour recall, and history of birth weight. The results show that there are still 11.4% of children under five who are undernourished as assessed using the calculation of the z-score index BB/TB. The data analysis used was the Pearson Correlation test with α = 0.05. Based on the results of statistical analysis tests, it was found that there was a significant relationship between carbohydrate, protein and fat intake and the nutritional status of toddlers. In addition, there is a significant relationship between vitamin A intake and the nutritional status of children under five, and there is no significant relationship between vitamin D, vitamin E, vitamin K and birth weight and nutritional status of children under five in Kanatang District, East Sumba Regency.